Mechanisms associated with possible vertical transmission of SARS-CoV-2 (Research, Society and Development, 2023)
Pregnancy associated with SARS-CoV-2 infection can be lethal for both mother and fetus, and prematurity is more frequent in infected patients. However, possible vertical transmission is still a divergent issue in the scientific environment, where the veracity and possible mechanisms are not yet fully established. We conducted a systematic review, previously registered in OSF (https://osf.io/ybt8x/?view_only=b62dc26ca157432dabcc56d40f9cc32a), using DeCS/MeSH descriptors and Boolean operators, in Embase, PubMed and Web of Science databases, with selection by screening and reading the full text, aiming to assess the occurrence of vertical transmission, with a focus on the outcome. We found that the expression of angiotensin-converting enzyme receptor 2 (ACE2) at the maternal-fetal interface involving the placenta and decidua, even if minimal, exposes a situation in which SARS-CoV-2 can invade, damage, and increase placental permeability, resulting in infectious involvement of the fetus. Transmission, when present, is not directly dependent on the severity of disease progression, even though there is an association of anti-SARS-CoV-2 IgM positivity with placental abnormalities and the severity of maternal disease. We conclude that there is a possibility of vertical transmission, even though there is controversy among authors, and also highlight the potentiation of vaccine antibody responses, exposing positive results for pregnant women and even for the fetus.